Multimodality of learning in higher education:Issues and challenges. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
Introduction and today’s borderless and globalised world, Educators are often faced with the arduous challenge Of preparing undergraduates with appropriate Competencies and practices so that they can cope in Workplaces which are increasingly Technologically-driven. Globalisation is placing new Demands on the kinds of ‘literacies’ we need in the Workplace as much as in the communicational demands Of everyday life.